Prospek Swasembada Beras di Provinsi Kalimantan Timur - Wajar Mey Handani; Nunung Kusnadi; Dwi Rachmina (Jurnal Agribisnis Indonesia, 2021)
Rice self-sufficiency in Indonesia remains a national priority program, since rice is a staple food of the majority of population. This national program has become an economic development agenda in almost all local governments at the provincial and district levels. East Kalimantan Province is one of the provinces that set the rice self-sufficiency on the local medium term planning (RPJMD) 2013-2018. This research generally aimed at analyzing the prospect of rice self-sufficiency in East Kalimantan Province. Specifically, the research aimed to measure the potential for developing rice in East Kalimantan Province and to analyze the production technical efficiency of rice farming. The data used in this research were national and provincial agriculture land area, and 337 units of rice farm from Agricultural Census 2013. Using LQ (Location Quotient) method indicated that economically rice was not a basic commodity of East Kalimantan Province. In the provincial level, there were only two out of four districs that had rice as basic commodity. Stochastic production frontier analysis showed that technical efficiency of rice production was 0.64, which indicated that rice production in the province was 36 percent below its production frontier. Planting patterns and land status significantly improved technical efficiency. From this research can be concluded that self-sufficiency program in East Kalimantan Province was not supported by regional potential of rice production nor by technically efficient rice production at the farm level.